The Impact of Digital Literacy on Indonesian Language Development - Chairunisa, Hera; Hasibuan, Hikmah Sakinah (Pusdikra-Publishing.com, 2024)
This study aims to explore the impact of digital literacy on Indonesian language development. Digital literacy is becoming increasingly important in the current digital era, with its widespread influence on various aspects of life including language. This research uses a qualitative research method with a descriptive approach to explain in depth and comprehensively about the influence of digital literacy on Indonesian language development. The descriptive method allows researchers to collect and analyze data in the form of words, pictures, and information from books, journals, and other relevant scientific works. This is in line with the research objective to gain an in-depth understanding of how digital literacy affects the use and development of Indonesians in various contexts. The results of this study show that the prospects and implications of digital literacy in the development of Indonesia, confirm the importance of using information and communication technology (ICT) to improve language skills. Digital literacy provides quick and broad access to various sources of information and learning materials in Indonesian, enabling users to create and share creative content on various digital platforms. In addition, digital literacy supports collaboration and social interaction, enables more innovative teaching methods, and increases awareness and appreciation of the Indonesian language.